Relationship of Behavior About Giving Solid Food With the Incidence of Gastrointestinal Infections in Children Aged 6-24 Months - Ketut Espana Giri; Rahmadhani; Fitni Hidayati; Arinda Lironika Suryana; Yayuk Sri Rahayu (CV. Get Press Indonesia, 2026)
Gastrointestinal infections are still one of the main causes of morbidity in children aged 6–24 months, especially during the period of complementary feeding (MPASI) that is not in accordance with the principles of hygiene and food safety. Maternal complementary feeding behavior, including timing, type, frequency, processing, and presentation, may increase the risk of gastrointestinal infections. This study aimed to analyze its relationship with gastrointestinal infections in children aged 6–24 months. This study uses an observational analytical design with a cross-sectional approach. The population is all mothers who have children aged 6–24 months who visit Andalas Padang Health Center. A sample of 120 respondents was selected by consecutive sampling technique. Behavioral data on MPASI administration were obtained through a structured questionnaire, while the incidence of gastrointestinal infections was measured based on a history of diarrhea in the last three months. Data analysis was conducted using chi-square test with a confidence level of 95%. The results showed that 58.3% of mothers had poor complementary feeding behavior, and 36.7% of children had gastrointestinal infections. There was a significant relationship between complementary feeding behavior and the incidence of gastrointestinal infections (p=0.002; OR=3.21; 95% CI=1.52–6.78). MPASI administration behavior was significantly associated with gastrointestinal infections, highlighting the need for improved education and nutrition counseling at Health Centers.